THE PREVENTATIVE TOOL OF HUMAN RIGHTS AND THE INCLUSIVITY OF SOGIESC FEELINGS - Jaba Kaplanishvili, (PEOPLE: International Journal of Social Sciences, 2025)
Refugees are vulnerable groups, and those based on their sexual orientation, gender identity and expression, and sex characteristics (SOGIESC) are even more vulnerable, due to their intersectional identities. Dr S. Chelvan created the Difference Stigma Shame Harm (DSSH) model that focuses on the SOGIESC grounds of the applicant and not their actual sexual practices. The phallometric test was banned as it was deemed to be ill treatment. The ABC case examined the right to dignity and prohibited videos as evidence, and the F case addressed the right of privacy and prohibited the homosexuality tests as evidence of someone’s SOGIESC. Thus, several methods of assessing someone’s SOGIESC have been prohibited, as they were not compliant with human rights standards. This paper argues that human rights law can be used as a preventive tool in assessing credibility. The DSSH model may seem more human rights-compliant, but it does not offer all the answers to the existing challenges in this field. The element of Shame seems not to be as inclusive as it should be, as it cannot be expected of every person to have developed the feeling of Shame, and the absence of this feeling has led to rejections of such claims. Thus, this paper suggests the replacement of that element with “feeling”, as people could have the fear of being persecuted based on their SOGIESC, but still experience different feelings that a heterosexual/cis person might not.